Peptide-Functionalized Nanomedicine: Advancements in Drug Delivery, Diagnostics, and Biomedical Applications - Hossein Omidian; Luigi X. Cubeddu; Renae L. Wilson (Molecules)
Peptide-functionalized nanomedicine has emerged as a transformative approach in precision therapeutics and diagnostics, leveraging the specificity of peptides to enhance the performance of nanocarriers, including gold nanoparticles, polymeric nanoparticles, liposomes, mesoporous silica nanoparticles, and quantum dots. These systems enable targeted drug delivery, molecular imaging, biosensing, and regenerative medicine, offering unparalleled advantages in bioavailability, cellular uptake, and therapeutic selectivity. This review provides a comprehensive analysis of peptide-functionalization strategies, nanocarrier design, and their applications across oncology, neurodegenerative disorders, inflammatory diseases, infectious diseases, and tissue engineering. We further discuss the critical role of physicochemical characterization, in vitro and in vivo validation, and regulatory considerations in translating these technologies into clinical practice. Despite the rapid progress in peptide-functionalized platforms, challenges related to stability, immune response, off-target effects, and large-scale reproducibility remain key obstacles to their widespread adoption. Addressing these through advanced peptide engineering, optimized synthesis methodologies, and regulatory harmonization will be essential for their clinical integration. By bridging fundamental research with translational advancements, this review provides an interdisciplinary roadmap for the next generation of peptide-functionalized nanomedicines poised to revolutionize targeted therapy and diagnostics.